Board structure and financial reporting quality of Nigerian listed deposit money banks - Gbadebo, A. (Journal of Economic Research & Business Administration, 2021)
Corporate governance is a theory in which management supervision facilitates the decision-making process, both in public and private organizations. The study investigated the outcome of board characteristics such as the board size and board composition, audit committee size, leverage, and firm size on earning management (financial reporting quality) in listed deposit money banks in Nigeria from 1999 to 2018. The study employed a panel regression technique to analyse the relationship between financial reporting quality and board structure. Also, to determine the appropriateness of the estimation technique to adopt Hausman tests was carried out. For the determination of earnings management and to separate nondiscretionary accrual (NDAC) constituents from the total accruals (TA) to arrive at discretionary accrual (DAC) components, the studies of the Jones model (1991), as modified by Dechow and Sloan (1995) used. The Hausman test result revealed that Random Effect was the most appropriate estimator, in line with the null hypothesis. It was confirmed by the Breusch-Pagan Lagrangian multiplier, while the Breusch-Pagan/Cook-Weisberg test confirmed no heteroskedasticity. Panel regression results showed that (board size and board composition) has a significant positive impact on financial reporting quality. However, audit committee size and Leverage have positive but insignificant relation. Besides, firm size has a significant adverse effect on the dependent variable. In contrast, Leverage has a positive but no impact on the financial reporting quality of deposit money banks in Nigeria. The inferences are that board size, board composition,n, and firm size are significant variables influencing Nigeria’s financial reporting quality. Therefore, the study recommends that banks and regulatory authorities check the excessive acquisition of assets and numerical increase in audit committee members to enhance commercial banks’ financial reporting quality in Nigeria. Key words: Board characteristics, Financial Reporting Quality, Deposit Money Banks.